Science at the Crossroads: The New Union South and the WID/MIR - Guthier, Mark (My University, 2007)
Mark Guthier, director of the Wisconsin Union, will describe plans for the New Union South and the "Science at the Crossroads" part of the WID/MIR building. Discussion will center on how science outreach programs can enhance their services through the use of these two buildings, which will open by 2011. This presentation is a part of "The New Constellation" seminar series, sponsored by The Center for Biology Education, the Science Alliance at UW-Madison, and WISCAPE. The title of the series refers to the forthcoming "bright spots" on campus for science outreach: the Microbial Sciences building (opens fall 2007), the WID/MIR building (opens 2010), the new Union South (opens 2011), and the renovation of Old Biochemistry.
Keywords: Wisconsin Union